PERBANDINGAN METODE FUZZY TIME SERIES HSU DAN DOUBLE EXPONENTIAL SMOOTHING PADA PERAMALAN NILAI TUKAR RUPIAH TERHADAP DOLAR AMERIKA - Anggraeni, Wulan (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2016)
The purpose of this study is to determine which accuracy is better between fuzzy time series method and Holt double exponential smoothing method. The data used is daily published rupiah exchange rate of Bank Indonesia in the period of 1 April 2016 until 17 june 2016. After being calculated, the error rate fuzzy time series Hsu method is at 0,6 %, while the error rate holt double exponential smoothing method is at 2,25%. Based on the calculation, it can be concluded that the error rate forecasting rupiah exchange rate using fuzzy time series method is lower than the holt double exponential smoothing It means that the fuzzy time series hsu method has better accuarcy than Holt double exponential smoothing method. The result of forecasting in 21, 22, 23, 24, and 25 respectively are Rp. 13355, Rp. 13375, Rp. 13395, Rp. 13465, Rp 13.475. Keywords: fuzzy time series, holt double exponential, forecasting